2021
DOI: 10.3389/fmolb.2021.583028
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 Has Potential to Be a Prognosis Marker for Cervical Squamous Cell Carcinoma and an Index for Tumor Microenvironment Change

Abstract: The tumor microenvironment (TME) has an essential role in the development of cervical squamous cell carcinoma (CSCC); however, the dynamic role of the stromal and immune cells is still unclear in TME. We downloaded data from The Cancer Genome Atlas (TCGA) database and applied ESTIMATE and CIBERSORT algorithms to measure the quantity of stromal and immune cells and the composition of tumor-infiltrating immune cell (TIC) in 253 CSCC cases. The protein-protein interaction (PPI) network and Cox regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…These changes were found for many cancers. Tian et al showed that CCR7 has the potential to be a prognosis marker for squamous cell cervical carcinoma cells and an index for tumor microenvironment change [85]. The CIBERSORT analysis showed a positive correlation between plasma cells, CD8 + T cells, and regulatory T cells and CCR7 expression within this study, suggesting that CCR7 could play a crucial role in maintaining the immunological dominance status for the tumor microenvironment [85].…”
Section: The Role Of Chemokines In Checkpoint Activation/inhibition In Cervical Cancersupporting
confidence: 57%
“…These changes were found for many cancers. Tian et al showed that CCR7 has the potential to be a prognosis marker for squamous cell cervical carcinoma cells and an index for tumor microenvironment change [85]. The CIBERSORT analysis showed a positive correlation between plasma cells, CD8 + T cells, and regulatory T cells and CCR7 expression within this study, suggesting that CCR7 could play a crucial role in maintaining the immunological dominance status for the tumor microenvironment [85].…”
Section: The Role Of Chemokines In Checkpoint Activation/inhibition In Cervical Cancersupporting
confidence: 57%
“…UV irradiation, particularly UVB, is one of the classical cellular stressors causing DNA damage in skins, which receives chronic sun exposure, and ultimately leading to skin development of cSCC [ 16 ]. Therefore, many present studies investigated the potential oncogenic role of molecules and pathways in cSCC and tried to evaluate the promising diagnostic biomarkers value for cSCC [ 17 20 ]. It is currently aimed to elucidate DNA binding/differentiation 4 (ID4) function in cSCC development [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of these four genes—CCR7, programmed cell death-1 (PD-1), ZAP70 and CD28—was linked to a better 5 year overall survival [ 97 ]. Further analysis of TCGA and protein–protein interactions supported a positive correlation between CCR7 expression in cervical squamous carcinoma cells and patient survival, which was linked to a predominant augmentation of immune-related pathways, as opposed to a more metabolic pathway described for the low CCR7 expression group [ 98 ]. Another recent analysis of TCGA database suggested an immune gene-related prognostic model for cervical cancer that includes CCR7, along with CD3d, CD3e, β2 integrin, family with sequence similarity 133 member A and p53 for forecasting survival and immune responses for cervical cancer patients [ 99 ].…”
Section: Ccr7 In Genitourinary Cancersmentioning
confidence: 99%